Risky Signals: The Political Costs of Exchange Rate Policy in Post‐Communist Countries. Issue 3 (24th February 2013) - Bagashka, Tanya; Stone, Randall W.
<x xml:space="preserve">Abstract</x> Bagashka, Tanya and Randall W. Stone. (2013) Risky Signals: The Political Costs of Exchange Rate Policy in Post‐Communist Countries. International Studies Quarterly, doi: 10.1111/isqu.12018 © 2013 International Studies Association It can be risky for governments to renege on exchange rate commitments, but it is misleading to characterize the costs as audience costs. While an audience costs approach assumes that the punishment for reneging is automatic, we model the choice of exchange rate policy in the shadow of elections as a signaling game between voters and governments, where governments have private information and voters are rational. We find that voters draw different inferences when they see reneging by different actors, and only Left governments are punished for breaking their promises. We test this hypothesis in the context of the post‐Communist countries from 1990 to 2007 and find that Left governments were more likely to fall if they reneged on exchange rate commitments, but Right governments were not.